Who’s Afraid of the Big Bad Math? Structure and Correlates of Math Anxiety in Preschool Children - Milovanović, Ilija; Adamov, Nikola; Popović, Lana; Blagojević, Sanja; Grković, Svetlana; Popović, Vanja; Grujić, Tanja; Isailović, Ivana (Psihološka istraživanja, 2025)
Math anxiety (MA) is a phenomenon that has garnered the attention of researchers and practitioners due to its negative effects on various educational outcomes in math learning and the motivation for learning math. However, previous research has predominantly focused on primary and secondary school students, while preschool-aged children have been largely overlooked. This gap is particularly relevant in the Serbian context, where early childhood education is undergoing continuous reforms and where mathematics readiness is increasingly recognized as a key predictor of later academic success. Therefore, this research aims to examine the structure and correlates of MA in preschool children from Serbia. Study 1, involving 258 children aged 4 to 6 (50% boys), investigated the nature and structure of the Young Children Math Anxiety Scale (YCMAX). Study 2, conducted with 205 children aged 4 to 6 (48.8% boys), investigated the relationships between MA aspects (Worry and Somatization), gender, age, and children’s readiness for learning math. This was done by applying the correlation analysis with the Mathematics School Readiness Test, designed to assess (pre)math skills in preschool-aged children. The CFA results indicate that the Young Children Math Anxiety Scale is an adequate instrument for measuring this type of anxiety and that, even at this age, negative relationships between MA and various (pre)math skills can be identified. The study discusses the potential benefits of using this scale by practitioners in preschool institutions and the specificities of the relationships between MA and various math abilities and children’s age in the preschool (non)evaluative contexts.